Using Baidu Index to Understand the Public Concern of Children’s Mental Health in Mainland China in the Context of COVID-19 Epidemic - Tan, Qinyi; He, Fang; Teng, Luyan (Journal of Education, Health and Sport, 2022)
This study aims to understand the temporal and spatial characteristics of public concern for "children’s mental health" in China in the context of the COVID-19 epidemic. Baidu Index is a research tool to collect and analyze massive data on Chinese netizens’ behaviors. Using Baidu Index as the research tool, this paper analyzes the trend and distribution of Chinese netizens’ attention to "children’s mental health" from December 1st, 2019 to March 20th, 2022 from three aspects of trend research, demand map, and crowd portrait. The study found that since the outbreak of COVID- 19, the search trend of "children’s mental health" has shown a cyclical change, peaking in May and valley around the Spring Festival and National Day, and stable in other periods. "Mental health", "handwritten newspaper on mental health" and "youth mental health" are the most popular buzzwords among the public. The groups concerned with "children’s mental health" is mainly distributed in Guangdong, Jiangsu, Beijing, and the majority are women between 30 and 39 years old. Meanwhile, search trends for "mental health" are like that for "children’s mental health." The factors influencing the search volume change of "children’s mental health" include Chinese traditional holidays, Spring Festival, National Day, Chinese Mental Health Day, and policies and instructions on children’s mental health issued by the PRC Ministry of Education. The public would like to know about "mental health", "handwritten newspaper on mental health" and "adolescent mental health".